Investigation of four wave mixing & cross gain modulation in photonic transmission system - Noor Faridah Mat Isa author (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2018)
The main purpose of the study is to investigate the nonlinear effects four wave mixing (FWM) and cross gain modulation (XGM) in wavelength division multiplexing (WDM) system. In addition, the study contributed the methods which are used to examine the impact of these effects on a transmission system consisting erbium doped fiber amplifiers (EDFAs) and a multiplex of coherent channels ; generally, this work is divided into two major parts. First, the investigation of FWM and XGM effects in transmission system. It also includes several modulation formats of DWDM system for return to zero (RZ), non return to zero (NRZ), and duobinary modulation format (DRZ). The second major objective is to reduce both of the nonlinear effects XGM and FWM in DWDM optical transmission system. The simulations are executed to optimize the device performance for the WDM system considering the limitation imposed by the nonlinear effects in multiwavelength systems with in line optical amplifiers and repeaters. Unequal channel spacing in multichannel transmitter and duobinary modulation technique is proposed in this researchto overcome this limitation.